Impact of cultivation strategy, freeze-drying process, and storage conditions on survival, membrane integrity, and inactivation kinetics of Bifidobacterium longum - Haindl, Regina; Neumayr, Alexandra; Frey, Anika; Kulozik, Ulrich (Folia microbiologica, 2020)
Bifidobacterium longum, one of the main microorganisms in the human gut, is used as an adjunct to lactic acid starter cultures or sold as a probiotic product. Therefore, Bifidobacterium longum cell suspensions get freeze-dried with protective additives to prevent activity losses. To date, investigations covering growth and inactivation kinetics of Bifidobacterium longum during the whole process (cultivation, drying, and storage) have been lacking. In this study, the effect of cultivation conditions and shelf temperature as well as the influence of protectants (maltodextrin, glucitol, trehalose) at various concentrations on cell survival during freeze-drying was assessed. Drying was followed by a storage at + 4 °C and + 20 °C for 70 days to evaluate inactivation kinetics. The impact of the different factors was assessed by measuring surival rate and residual moisture content at various points of time over the whole process. In parallel cell membrane integrity and glass transition were determined to reveal inactivation effects. Cultivation strategy had a strong influence on survival with a huge potential for process improvement. A pH of 6.0 at the growth optimum of the strain provides better conditions regarding cell survival after drying than free acidification (non-regulated pH conditions). During the drying step, membrane leakage due to the removal of water is the main reason for the inactivation in this process step. In this study, the highest survival of 49% was obtained with cells dried at + 35 °C shelf temperature with an addition of maltodextrin (75% bacterial dry matter, w/w). The results show that Bifidobacterium longum cells are mostly inactivated during drying, whereas storage conditions at + 4 °C with an addition of 75% BDM maltodextrin relative to bacterial dry mass prevent cell loss completely.
Keywords: kinetika; Desiccation; polysacharidy; Cell Culture Techniques; lidé; Microbial Viability; koncentrace vodíkových iontů; mikrobiální viabilita; Protectants; vysoušení; probiotika; sorbitol; Probiotics; Trehalose; trehalosa; Sorbitol; Humans; Hydrogen-Ion Concentration; Temperature; Membrane preservation; Kinetics; Bifidobacterium longum; kultivační média; Storage temperature; lyofilizace; buněčné kultury; Maltodextrin; Polysaccharides; Freeze Drying; teplota; Bifidobacterium longum ssp. longum Reuter 1963; Culture Media